An African pygmy hedgehog adenovirus 1 (AhAdV-1) outbreak in an African pygmy hedgehog (Atelerix albiventris) colony in Japan. (June 2020) - Ochiai, H.; Tamukai, K.; Akabane, Y.; Oba, M.; Omatsu, T.; Okumura, A.; Mizutani, T.; Madarame, H.
Highlights: A novel adenovirus outbreak occurred in a colony of African pygmy hedgehogs (APHs). An African pygmy hedgehog adenovirus 1 (AhAdV-1) infection was confirmed in 13 APHs. AhAdV-1 was isolated from one APH. Five APHs died during the outbreak and AhAdV-1 can cause fatal pneumonia in a case. AhAdV-1 should be monitored as a potential cause of emerging infections in APHs. Abstract: An African pygmy hedgehog adenovirus 1 (AhAdV-1) outbreak in a colony of 24 African pygmy hedgehogs (APHs) with a case of fatal pneumonia occurred in Japan. Thirteen out of a colony of 15 APHs with respiratory symptoms were diagnosed with AhAdV-1 infection based on the detection of AhAdV-1 genome in throat/nasal swabs and further one APH was diagnosed on isolation of the virus. Five infected APHs died during the outbreak and AhAdV-1 caused severe pneumonia and death in one case. After the outbreak, persistent AhAdV-1 infection was suggested in one surviving APH. AhAdV-1 is a novel adenovirus and is suspected to be an emerging pathogen.